The Effect of the Effectiveness of the Implementation of Smart State Civil Apparatus (ASN) ON Bureaucratic Reform in the Era of Disruption 4.0 in the Regional Civil Service Agency of Banten Province - Indah Pusparani; Ayuning Budiati; Rina Yulianti (Syntax Idea)
Along with the running of the wheels of government in Indonesia, there are many developments that occur in various aspects, one of which is in government, economy, development and politics. Originally in the old order era, the new order until the reform there were many changes that accompanied the journey of this country, both happy and sad changes. The type of research used in this study is quantitative research. Quantitative research methods are one type of research whose specifications are systematic, planned and clearly structured from the beginning to the making of the research design. Based on the results of research and discussion on How Much the Effect of the Effectiveness of Smart ASN Implementation on Bureaucratic Reform in the Era of Disruption 4.0 in the Regional Civil Service Agency of Banten Province, it can be concluded that the Effect of the Effectiveness of Smart ASN Implementation on Bureaucratic Reform in the Era of Disruption 4.0 in the Regional Civil Service Agency of Banten Province has an influence of 64.7%, while the remaining 35.5% where the rest is influenced by other variables that are in The study was not analyzed further